Coping with the Dutch Disease - The Case of Norway - Ehrs, Mikael (My University, 2007)
Norway is a net exporter of oil and natural gas, the third most important petroleum exporting country in the world. The sales create considerable resource revenue for the Norwegian State, amounting to hundreds of billion NOK every year. However, this great resource wealth also makes Norway vulnerable to an unusual economic affliction, known as the Dutch Disease – the crowding out of a country’s manufacturing sector by the resource extraction sector. The Dutch Disease theory assumes that the resource sector – by means of the resource movement effect, the spending effect and the spillover-loss effect – will compete with the manufacturing sector in demand for labour and services, appreciate the real exchange rate, and eliminate some of the industrial know-how and learning-by-doing. The resulting loss of industrial competitiveness on the international market seriously weakens the country’s manufacturing sector. However, despite possessing all the prerequisites for contracting the disease, Norway has over the last thirty years proved remarkably resistant to it – maintaining a strong manufacturing sector and keeping wage increases at a moderate level. This thesis studies the policies Norway have adopted to battle the disease during the last three decades, to see if their successes can be generalized and implemented in other resource producing countries. The conclusion is that some of Norway’s success did come from factors specific to Norway, such as the country’s highly centralized wage formation system and the capital-intensive nature of North Sea oil – but other policies could in fact be considered universal. A good example of such a Norwegian policy is the formation of a special reserve fund for the resource rents, created to shield the economy from the spending effect.
Keywords: Dutch Disease; Norway; oil; resource extraction; manufacturing; fi=Kansantaloustiede|en=Economics|